Perbedaan Kecerdasan Emosional pada Mahasiswa yang Mengikuti UKM Musik dan Mahasiswa yang Mengikuti UKM Non-Musik - Annisa Aulia Putri; Haryanto Haryanto (Faculty of Psychology, Universitas Gadjah Mada, 2018)
The purpose of this research was to determine differences in emotional intelligence between students participating in music extracurricular activities with non-extracurricular students. This research used a quantitative method with the Emotional Intelligence Scale to measure the emotional intelligence. The hypothesis was that students participating in musical extracurricular activities showed higher emotional intelligence than students with non-musical extracurricular. Total participant of this study were 83 active student members of the extracurricular groups in Universitas Gadjah Mada. Independent T-test, found that there’s no significant difference between students from musical extracurricular than non-musical extracurricular(t = 1,443; p> .05. Finding does not support positive relationship between participation in music extracurricular activities and emotional intelligence.